2007
DOI: 10.1111/j.1540-8167.2007.00928.x
|View full text |Cite
|
Sign up to set email alerts
|

The VA Relationship After Differential Atrial Overdrive Pacing: A Novel Tool for the Diagnosis of Atrial Tachycardia in the Electrophysiologic Laboratory

Abstract: The delta-VA interval was useful for diagnosing AT irrespective of patient conditions such as ventriculoatrial conduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 18 publications
(39 reference statements)
1
58
0
1
Order By: Relevance
“…Previous studies have utilized overdrive atrial pacing from different sites. One study has shown that a difference in VA R and VA T of less than 14 milliseconds when performing differential pacing from high right atrium and proximal CS is diagnostic of AVNRT or AVRT and excludes all patients with AT . In our patient the corresponding values with these two maneuvers are 0 milliseconds (160–160 milliseconds) and 1 millisecond (161–160 milliseconds), respectively.…”
Section: Commentarymentioning
confidence: 99%
“…Previous studies have utilized overdrive atrial pacing from different sites. One study has shown that a difference in VA R and VA T of less than 14 milliseconds when performing differential pacing from high right atrium and proximal CS is diagnostic of AVNRT or AVRT and excludes all patients with AT . In our patient the corresponding values with these two maneuvers are 0 milliseconds (160–160 milliseconds) and 1 millisecond (161–160 milliseconds), respectively.…”
Section: Commentarymentioning
confidence: 99%
“…Thus, at least in electrophysiology, change is good. Diagnostic criteria have been developed for the many changes that occur during an SVT study—changing from sinus rhythm to SVT; the onset of burst pacing from ventricle or atrium during SVT; resumption of tachycardia at the end of burst pacing during SVT from ventricle or atrium; delivery of extrastimuli from ventricle or atrium during SVT; spontaneous variation in SVT cycle length; development or relief of bundle branch block during SVT; response to drug administration; and termination of SVT to sinus rhythm . At least 40 different pacing maneuvers or observations have been described in this area.…”
Section: Editorial Commentmentioning
confidence: 99%
“…38,39 DIFFERENTIAL-SITE ATRIAL PACING. Rapid atrial pacing results in overdrive suppression of the AT rate.…”
Section: Diagnostic Maneuvers During Tachycardia Atrial Extrastimulatmentioning
confidence: 99%